Inpatient Service Procedures for Insurance and Non-Insurance Patients at National Hospital Surabaya - Rimo Eko Saputro; M. Hidayat; Handyka Prayogi Lesmana (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
The research aims to make it easier for patients to get comprehensive health services and establish patient diagnoses and plan appropriate therapy for patients. The research method uses empirical normative methods, which means research whose object of study is aimed at written regulations and valid data in the field so that this research is very closely related to libraries and data in the field. The results of the research on legal protection for patients are listed in Law Number 36 of 2009 concerning Health, Law Number 29 of 2004 concerning Medical Practice, Law Number 44 of 2009 concerning Hospitals, and because patients are consumers of services, provisions also apply in Law Number 8 of 1999 concerning Consumer Protection. The relationship between the patient and the hospital is a civil law relationship. If one party defaults, the other party, in this case the patient, can file a lawsuit/claim for compensation against the default party. The provisions of Article 1365 can also be used as a reference for patients to make claims for compensation against hospitals or health workers, because they have caused harm to patients, both physically and non-physically.